Review: Time Use as an Explanation for the Agri-Nutrition Disconnect: Evidence from Rural Areas in Low and Middle-Income Countries. (April 2018) - Johnston, Deborah; Stevano, Sara; Malapit, Hazel J.; Hull, Elizabeth; Kadiyala, Suneetha
Highlights: Women play a key role in agriculture, as reflected in their time commitments. Our limited evidence suggests agricultural interventions may sometimes increase time commitments. Changing time use changes nutritional outcomes in a range of complex ways. Abstract: Time is a vital input into nutritional outcomes, as it is necessary for the production, procurement and preparation of food, child feeding and childcare. Thus, agricultural interventions may fail to improve nutritional outcomes if they do not take account of time constraints, particularly of rural women who spend a considerable portion of their time in agriculture. Given the potential trade-offs pertaining to time in productive vs. reproductive activities and its implications for maternal and child nutrition, the goal of this review is to systematically map and assess the available evidence, both qualitative and quantitative studies, agriculture-time use-nutrition pathway. Through an analysis of 89 studies, identified through a systematic search, on rural areas of low and middle-income countries, we observe three findings. First, women play a key role in agriculture, as reflected in their time commitments. Second, evidence from a very limited set of studies suggests that agricultural interventions tend to increase time commitments in agriculture of the household members for whom impact is measured. Third, while changing time use tends to change nutritional outcomes, it does so in a range of complex ways and there is no agreement on the impact. Nutritional impacts are varied because households and household members respond to increased time burden and workload in different ways.